Radix Astragali and Radix Angelicae Sinensis in the Treatment of Idiopathic Pulmonary Fibrosis: A Systematic Review and Meta-analysis - Zhang, Yufeng; Gu, Lina; Xia, Qingqing; Tian, Lijun; Qi, Jia; Cao, Mengshu (Frontiers in Pharmacology, 2020)
Introduction: There are many clinical studies in the treatment of idiopathic pulmonary fibrosis (IPF) with herbal medicine included Radix Astragali (RA) and Radix Angelicae Sinensis (RAS) and has obtained good curative effect. There is no systematic evaluation on the clinical efficacy of RA and RAS in patients with IPF. The aim of this systematic review and meta-analysis was to critically evaluate the current evidence of efficacy and safety of RA and RAS in IPF. Methods: We searched the primary database for randomized controlled trial (RCT) of RA and RAS treating IPF. We assessed the quality of included studies using the Jadad rating scale and referred to the Cochrane Reviewer’s Handbook for guidelines to assess the risk of bias. We extracted the main outcomes of included RCTs and a meta-analysis was conducted using the Cochrane Collaboration’s RevMan5.3 software. Results: Seventeen eligible RCTs were identified and made a systematic review and meta-analysis. Risk of bias and quality of included RCTs were carried out. The results of meta-analysis showed that total effective rate and traditional Chinese medicine syndrome effective rate were statistically significantly higher in experimental group than control group, main pulmonary function index, six minute walking distance and Borg scale questionnaire score were statistically significantly better in experimental group than control group and adverse reactions was statistically significantly lower in experimental group than control group. Conclusion: RA and RAS are effective and safe in the treatment of IPF, which is beneficial to pulmonary function and exercise tolerance of these patients.